2014
DOI: 10.1177/0031721714557450
|View full text |Cite
|
Sign up to set email alerts
|

Creating digital authors

Abstract: Elementary students find themselves engaged and learning at a digital writing camp. The authors find that such elementary students usually have limited access to technology at home and school, and posit that teachers should do all they can to give them more access to and experience in digital composing. Students were motivated and learned to use technology through experimentation and collaboration, the authors said, adding that technology had a positive effect on the students’ writing process and final product… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 5 publications
0
1
1
Order By: Relevance
“…Whether there is a significant difference between the high school students' attitudes towards digital writing and writing on paper was also investigated in Gül's study, and a difference was found in favor of attitudes towards digital writing, albeit not statistically significant. This result is different than the results of the relevant studies available in the literature, in which a statistically significant difference was reported in favor of digital writing between the two types of writing [23], [24]. This discrepancy in results may be attributed to the finding reported by many studies conducted in Turkey that the teachers do not pay due attention to the use of digital writing skills in their lessons, and that they generally continue to enforce the practice of writing on paper [20], [28].…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Whether there is a significant difference between the high school students' attitudes towards digital writing and writing on paper was also investigated in Gül's study, and a difference was found in favor of attitudes towards digital writing, albeit not statistically significant. This result is different than the results of the relevant studies available in the literature, in which a statistically significant difference was reported in favor of digital writing between the two types of writing [23], [24]. This discrepancy in results may be attributed to the finding reported by many studies conducted in Turkey that the teachers do not pay due attention to the use of digital writing skills in their lessons, and that they generally continue to enforce the practice of writing on paper [20], [28].…”
Section: Discussioncontrasting
confidence: 99%
“…In particular, typing is highlighted as a convenient feature of digital writing and indicated as a reason why it is preferred over writing on paper. It has been reported that the short-term memory is used more efficiently in digital writing, as it is less tiring than writing on paper [23]. Similarly, in another study, it was stated that digital writing does not increase the mental load, and thus that the quality of the products produced via digital writing is not affected negatively [24].…”
Section: Introductionmentioning
confidence: 93%